Akdang langaw ni kristian s. cordero- gawad palanga: isang pagsusuri - Toriente, Sarah Jane Q. (San Miguel, Iriga City: University of Saint Anthony, 2023)
Akdang langaw ni kristian s. cordero- gawad palanga: isang pagsusuri
Includes bibliographical references.
Tagalog
Keywords: Akdang langaw, gawad palanga